Terapi Spiritual Untuk Meningkatkan Quality Of Life Pasien Yang Menjalani Hemodialisis : A Literature Review - Riris Risca Megawati; Arlies Zenitha Victoria; Dwi Fitriyanti (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2021)
Patients chronic kidney failure (CKD) with hemodialysis can affect the quality of life (quality of life). This is due to an imbalance between physical, psychological, social, and spiritual. Hemodialysis patients experience psychiatric disorders and coping problems, which can pose a serious threat to their physical and mental health. Apart from physical and psychosocial aspects, spiritual aspects also need to be maintained. Through spiritual means, CKD patients can express their feelings, desired hopes and trust in God. Spiritual therapy was one of the actions to improve the quality of life of hemodialysis patients. Spiritual therapy can increase hope and meaning in life, self-confidence, quality of life, and reduce patient anxiety. This literature review aimed was to an understanding of spiritual healing in improving the quality of life of patients undergoing hemodialysis. The method were used an electronic database of journals published through Proquest, EBSCO, PubMed, and Google Schoolar. The keywords were used Spiritual, Quality of Life, and Hemodialysis. The results of a review of 7 journals that have been selected state that spiritual therapy can improve the quality of life of patients undergoing hemodialysis. The most widely used spiritual therapies were SEFT (Spiritual Emotional Freedom Technique), Qur'anic Therapy (Islamic Bibliotherapy), Murottal, spiritual guidance, sleep hygiene and deep breathing with spiritual care, and the holy qur'an. Patients undergoing hemodialysis are proven to be effective in improving the quality of life through spiritual therapy. Spiritual therapy is very important to improve the patient's quality of life, because it can overcome anxiety and make the mood more peaceful and calm.Keywords: hemodialysis; quality of life; therapy spiritual